Acanthephyra stylorostratis - Cardoso, Irene; Contents, Paulo Young Table Of (Zenodo, 2005)
Acanthephyra stylorostratis (Bate, 1888) (Figs 19–23) Bentheocaris stylorostratis Bate, 1888: 726, pl. 123, fig. 4. Acanthephyra stylorostratis — Calman, 1925: 14; Chace, 1936: 30; 1940: 144, fig. 22; 1986: 10. Material examined: Revizee Program: E0538, 20 o 27'S, 39 o 38'W, 1680m, 1 male (15mm), MNRJ 14845. Diagnosis: Carapace with a thin crest that projects in a rounded rostrum with six spiniform teeth dorsally, anterior one styliform and longer than others; antennal spine small; branchiostegal spine supported by a long carina, reaching 2/3 of carapace. Abdomen dorsally carinate on all somites, except on somite 1; somites 3 to 6 with posteromesial tooth; the one of somite 3 distinctly strong. Male pleopod 1, endopod rounded, with numerous long, stout setae on anterior margin, and a distal lobe with hook setae. Male pleopod 2, appendix interna 1 ¼ length of appendix masculina, apex triangular with hook setae; appendix masculina with rounded apex, acute, simple setae on distal margin. Description: Eyestalk slightly shorter than styliform tooth of rostrum, with dorsal protuberance, without ocellus on mediodistal portion (Fig. 19B). Carapace with a thin laterally compressed crest that projects over the frontal margin in a rounded rostrum, with six spiniform teeth dorsally, anterior styliform tooth longer than others; rostrum reaching 1/6 of scaphocerite; carapace carinate on posterior end; small antennal spine present; branchiostegal spine supported by a long carina, reaching 2/3 of carapace; supraorbital and pterygostomian spines absent; cervical groove present; suprabranchial carina absent (Fig. 19A). Stylocerite broad, acute apex reaching end of first antennular peduncle article; first antennular peduncle article with distal margin serrate, tooth on outer margin reaching end of second antennular peduncle article; second antennular peduncle article with tooth on outer margin reaching 1/3 of third antennular peduncle article (Fig. 19C). Scaphocerite with blunt apex, densely plumose setae on inner margin and small distal tooth on outer margin (Fig. 19D). Mandible with palp threearticulated; incisor process with eight teeth, molar process triangular, with row of simple, short setae (Fig. 20A, B). Maxilla 1 with two endites, distal endite with numerous stout, serrate setae on inner margin; basal endite with pappose setae on distal margin, long, stout, pectinate setae on inner margin and several pappose setae on basal margin; palp with several pappose setae on rounded apex and one stout seta (Fig. 20C). Maxilla 2 with two endites, distal endite bilobed, both lobes with pectinate setae on inner margin; basal endite rounded, densely plumose setae on inner margin; endopod longer than endites, pappose setae on apex; scaphognathite with densely plumose setae on all margins (Fig. 20D). Maxilliped 1 endite with pappose setae on distal margin and pectinate setae on inner margin; endopod threearticulated, longer than distal endite, several pappose setae on apex and inner margin; exopodal lobe with densely plumose setae on margins (Fig. 20E). Maxilliped 2 endopod with elongate ischium and merus, pappose setae on inner margins; carpus short; propod rounded, pectinate setae on distal margin and long, stout, pectinate setae on inner margin; dactyl with long, stout, pectinate setae on inner margin; exopod with densely plumose setae on all margins (Fig. 20F). Maxilliped 3 slender, elongate; propoddactyl with stout setae in apex; exopod with densely plumose setae on all margins (Fig. 20G). Pereopods 1 and 2 chelate. Pereopod 5 merus with 13 stout setae on inner margin (Fig. 19A). Epipods with mesial teeth present on pereopods 1 to 3 (Fig. 21A, B). Abdomen dorsally carinate on all somites, except on somite 1; somites 3 to 6 with posteromesial tooth; the one of somite 3 distinctly strong; somite 6 at least 1 ½ times longer than high (Fig. 19A). Male pleopod 1 endopod rounded, with numerous stout setae on anterior margin, distal lobe with numerous hook setae (Fig. 21C). Male pleopod 2 with appendix masculina shorter than appendix interna, with numerous acute pectinate setae on distal margin; appendix interna, about 1 ¼ length of appendix masculina, with apex slightly triangular with hook setae (Fig. 21D). Telson not sulcate in dorsal midline, with two pairs of dorsolateral stout setae, and three pairs of distal setae, median pair stronger (Fig. 22A, B). Distribution: Western Atlantic: U.S.A. (off New Jersey), Mexico (Gulf of Mexico), Brazilian coast (21 o 12'S; 40 o 00'W). Eastern Atlantic: Canary, Madeira and Cape Verde Islands. Indian and Pacific: South Africa (Natal), Tuamotu Archipelago. Adults probably are mesopelagic (Barnard 1950; Chace 1986; Wasmer 1986). Remarks: Acanthephyra stylorostratis occurs in the Indian, Pacific and Atlantic Oceans. In the Western Atlantic, this species was recorded on North and Central America. This is the first record of this species from the Brazilian coast (South America) (Fig. 23). Acanthephyra gracilipes does not have a dorsal carina on abdominal somite 2, and the dorsal tooth on abdominal somite 3 is low and curved to left, while A. stylorostratis has a dorso dorsal carina on abdominal somite 2, and the dorsal tooth on abdominal somite 3 is not curved. In Brazilian waters, A. acutifrons, A. eximia, A. quadrispinosa and A. stylorostratis occur. Acanthephyra stylorostratis differs from A. eximia and A. acutifrons in the rostrum shape, in the presence of branchiostegal carina, and by the smaller carapace length. Acanthephyra stylorostratis differs from A. quadrispinosa in the rostrum shape, in the presence of dorsal carina on carapace and by the longer branchiostegal carina (Table 1). The material examined agrees with the description of Bate (1888) in the rounded rostrum, with dorsal small teeth and the apical styliform tooth, and in the carapace and abdominal somite 2 to 6 being carinate. The material examined agrees with the descriptions of Chace (1940), Barnard (1950) and Wasmer (1986) except for three dorsolateral stout setae on telson compared to only two pairs of dorsolateral stout setae on the present material. : Published as part of Cardoso, Irene & Contents, Paulo Young Table Of, 2005, Deep-sea Oplophoridae (Crustacea Caridea) from the southwestern Brazil, pp. 1-76 in Zootaxa 1031 (1) on pages 27-33, DOI: 10.11646/zootaxa.1031.1.1, http://zenodo.org/record/5050357 : {"references": ["Bate, C. S. (1888) Report on the Crustacea Macrura collected by the Challenger during the years 1873 - 76. Report on the Scientific Results of the Voyage of H. M. S. \" Challenger \" during the years 1873 - 76, 24, 1 - 942.", "Barnard, K. H. (1950) Descriptive catalogue of South African Decapod Crustacea. Annals of the South African Museum, 38, 1 - 837.", "Chace, F. A. (1986) The Caridean shrimps (Crustacea: Decapoda) of the Albatross Philippine Expedition, 1907 - 1910, part 4: families Oplophoridae and Nematocarcinidae. Smithsonian Contributions to Zoology, 432, 1 - 82.", "Wasmer, R. A. (1986) Pelagic shrimps of the Family Oplophoridae (Crustacea Decapoda) from the Pacific sector of the southern Ocean: USNS Eltanin Cruises 10, 11, 14 - 16, 19 - 21, 24 and 25. In L. Kornicker (Ed), Biology of the Antarctic Seas XVII, Antarctic Research Series, Washington, 44: 29 - 68.", "Chace, F. A. (1940) Plankton of the Bermuda Oceanographic expeditions, IX: The Bathypelagic Caridean Crustacea. Zoologica, 25 (2), 117 - 209."]}